(untitled) (Fiep Bulletin - online, 2013)
The study it comes to identify the possibilities to manage sociological theories on the internal logic that commands the sport, mainly when we take in consideration to the social relations of “Identity” and “Nationalism” in the use politician of the passion, that is, to be able and violence - fear, hope and happiness, in the constructions of the behaviors and respective behaviors of a people. Initially, two argumentative considerations appear to guide the development of the thematic one: First: The sport have proper ethics in relation to the ethics politics, as to understand the relation of the Modern Sport in a society where the globalization process meets each ascending time in the constructions of the behavior and social behaviors? Second: How to contextualize the soccer in the educative and formatter correlation of behaviors and behaviors proclaimed by cultural history in the construction of the Brazilian society? Ahead of these consideration and questions, as well as of possible formulated hypotheses, we objectify to analyze the nature of the sport in Brazil, cultural phenomenon that have left to hang doubts with regard to its concretely educative and formatter of social behaviors and behaviors. Breaking of an international vision of landmarks partner-descriptions of the sport we carry through apprehensions of authors as Max Weber (1967), Eric Hobsbawm (1992) , Norbert Elias (1990/1993), amongst others, to glimpse the dimensions of the sportive field in the process of the social relations which exert influences in the construction of the societies. We detach the studies accomplished in Brazil, its bonds and connections of the Sport and Society. We introduce the relearning of the studies on the “Social Dimensions, Politics, Economic and Cultural of the Field of the Sport”, according to Di Giovanni, Proni, Gebara (1995). The carried through clipping mentions the organization to it of the soccer in Brazil, in the form of presentation of the spectacle, in the crises and the occurred transformations in the scope of social reactions fundamental segments in the mass events. Thus, Elias will use itself of the philosophical analysis - sociological of Norbert (1990/1993) to effect theoretical managements to the formation of behaviors and collective behaviors, where after all of accounts, it bases the study of the sprouting and popularizes of the soccer on Brazil.